Integrative data reveal a new millipede species of Sinocallipus Zhang, 1993 (Callipodida, Sinocallipodidae) from Vietnam, with notes on its phylogeny - Anh D. Nguyen; Pavel Stoev; Tam T. T. Vu (Zoosystematics and Evolution)
The callipodidan genus Sinocallipus Zhang, 1993 (Callipodida, Sinocallipodidae) is reviewed within the scope of the Vietnamese fauna. A total of three species are recorded in Vietnam including a new one, Sinocallipus similis sp. nov. All three species are confirmed by morphological and molecular data. An existing identification key of Sinocallipus species is amended to include the new species.